Corporate commitment to water sustainability: determinants of water disclosure in the agricultural and healthcare sectors in Malaysia - Mohamad, Noor Afzalina; Samsudin, Zaira Aniza; Salleh, Zalailah; Zalailah Salleh1 , Norakma Abd Majid, Norakma; Sh Ahmad, Siti Norsakinah (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
Addressing the corporate water sustainability is crucial for both firms and stakeholders. Over the past decade, various analysis on Malaysian firms in agricultural and healthcare sectors have been conducted, focusing on their varying degrees of water sustainability, although studies on water disclosure are limited. This study explored corporate water sustainability by investigating the determinants of corporate water disclosure among publicly listed firms in Malaysia’s agricultural and healthcare sectors. Utilizing a quantitative research approach and regression analysis, the results indicated that ISO 14001-certified firms exhibited significantly higher levels of water disclosure. Firms that were Shariah compliant also disclosed more water-related information than non-compliant firms, reinforcing the view that Shariah status supported ethical conduct and sustainability disclosure practices. The empirical evidence demonstrating that externally imposed expectations - whether through environmental management standards or ethical governance requirements can influence corporate disclosure behaviour, which consistent with the Stakeholder Theory. The analysis further revealed that agricultural firms disclosed more water information than those in the healthcare sector, reflecting the higher water sensitivity and stakeholder scrutiny in the agriculture sector.